Bouncing back after trauma: music therapy, gender, and mental health in conflict-ridden settings - Ali Bitenga Alexandre; Amani Kasherwa; Juvenal Bazilashe Mukungu Balegamire; Jonathan Yoyu Tunangoya; Lampard Omari Mukanga; Freddy Zihindula Buhendwa; Marc Ombeni Rusagulira; Masheka Mirango Hilaire; Phillipe Amani Busane; Gilbert Mubalama Mugisho; Denis Mukwege Mukengere (Discover Mental Health)
Abstract Background The aim of this study was to assess the impact of music therapy with songwriting on mental health of vulnerable women and men in a conflict-ridden setting. We examine the impact on participants’ mental health (specifically anxiety, depression and post-traumatic stress disorder symptoms), the extent to which improvement was sustained for an extended period of time, and whether there were gender differences in improvement. Such an assessment is central in appraising the strength and relevance of mental health services offered to vulnerable populations in conflict-ridden settings. Methodology This study is a longitudinal mixed method evaluation of music therapy with songwriting comparing mental health symptoms of participants before and after exposure to the program rather than a clinical trial with a control group. Participants in the Healing in Harmony (HIH) program were screened for anxiety, depression and PTSD before treatment, immediately after treatment and 6 months later. The Hopkins Symptoms checklists were used to evaluate anxiety and depression among 128 women and 60 men exposed to the HIH program from April to August 2021 in Mulamba in eastern DRC. The Harvard Trauma Questionnaire was used to measure post-traumatic stress disorder (PTSD). Average scores range from 1 to 4, with higher values indicating higher levels of the symptoms. Participants were classified as positive for each outcome when they scored equal to 1.75 or higher for anxiety and depression, and 2.5 or higher for PTSD. The qualitative component of the study  draws from   four focus group discussions (FGDs), two of which were conducted immediately after treatment and two six months later to gain an in-depth understanding of participants’ experiences with the HIH. Results At the aggregate level, the rates of anxiety, depression and PTSD before treatment among participants were respectively 91.4, 90.4 and 36.7%. Immediately after treatment, the rates dropped significantly to 14.3, 15.9 and to 2.1%, respectively. The mean scores of the three mental health disorders were high before treatment but dropped significantly after treatment. The aggregate mean scores for anxiety, depression, and PTSD before and after treatment were 2.55 vs 1.29, p < 0.001, 2.38 vs 1.35, p < 0.001 and 2.27 vs 1.30, p < 0.001, respectively. The only statistically significant difference between men and women was the mean score of depression before treatment (women 2.44 vs men 2.24, p < 0.05). Both men and women demonstrated statistically significant improvement in mental health immediately after treatment across all categories (p < 0.001). Six months after treatment, aggregate scores show that improvement was sustained across all categories. For depression and PTSD, scores showed a small but statistically significant improvement over the immediate post-treatment scores (by 0.03 and 0.01, respectively, p < 0.05), while anxiety scores showed a small but statistically significant increase in symptoms (by 0.16, p < 0.05). Although women appear to show signs of greater and longer-lasting improvement compared to men, these differences are not statistically significant. Findings from the qualitative component of the study suggest that men’s inclusion in psychosocial rehabilitation programs previously designed for women is crucial in our efforts to establish trauma-free environments, and for constructing healthy gender relationships across time and space. Conclusion Findings suggest that the HIH program improves mental health disorders for both women and men, and that including men in a program originally designed for women might enhance mutual understanding between women and men contributing to effective and sustainable healing. Clinical trials are needed for future research to examine the impact of men’s inclusion in women’s originally designed mental health interventions.